Menguak Makna Akuntabilitas dalam Mengelak Lika-Liku Fraud: Studi Fenomenologi pada Tourist Village - Suryani, Pesi; Ginting, Rafles; Daurrohmah, Eka Wirajuang (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This study explores the revenue of Tourism Villages in Bali Province and the important role of financial management and reporting in preventing accounting fraud. Tourism villages in Bali are considered as potential communities in local tourism development and major contributors at the regional level. Identified revenue sources include rental of tourist attractions, tour packages, entrance tickets, and foreign tourist donations. The role of financial reporting in resource accountability and performance evaluation is explained. Transparency and accountability are implemented to maintain financial integrity and involve community participation in oversight. Local culture, particularly the Tri Hita Karana concept, is identified as a key factor in preventing accounting fraud through the internalisation of ethical values. This research also highlights the fraud prevention system involving detectors, assessors, effectors, and communication networks. The results showed the successful implementation of transparency, accountability, local culture, and prevention system in avoiding accounting fraud in the financial management of tourist villages. This study provides insights for tourist village managers and policy makers to improve honest and accountable financial management, support sustainable development, and maintain the integrity of tourist villages as valuable assets in Bali's tourism industry.